2020
DOI: 10.2147/dmso.s264830
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long Non-Coding RNAs in Brown Adipose Tissue</p>

Abstract: Obesity has become a widespread disease that is harmful to human health. Fat homeostasis is essentially maintained by fat accumulation and energy expenditure. Studies on brown adipose tissue (BAT) represent a promising opportunity to identify a pharmaceutical intervention against obesity through increased energy expenditure. Long non-coding RNAs (lncRNAs) were thought to be critical regulators in a variety of biological processes. Recent studies have revealed that lncRNAs, including ones that are BAT-specific,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 89 publications
(131 reference statements)
1
7
0
Order By: Relevance
“…We classified DELs into different clusters using the k-means method. The BAT is specialized for energy expenditure and heat generation, which depends on the function of mitochondria [45]. Purine nucleotides proved a constitutive inhibitor of UCP1 mediated proton conductance of the mitochondrial inner membrane and constituted the default shut-off mechanism in the absence of thermogenic demand [46].…”
Section: Discussionmentioning
confidence: 99%
“…We classified DELs into different clusters using the k-means method. The BAT is specialized for energy expenditure and heat generation, which depends on the function of mitochondria [45]. Purine nucleotides proved a constitutive inhibitor of UCP1 mediated proton conductance of the mitochondrial inner membrane and constituted the default shut-off mechanism in the absence of thermogenic demand [46].…”
Section: Discussionmentioning
confidence: 99%
“…lncRNA-BATE10 is BAT-specific and is a member of the lncRNA-BATE family. lncRNA-BATE10 is transcribed from four exons in an intergenic region of mouse chromosome 18 and is ~1.7 kb in length (21). lncRNA-BATE10 expression in white adipose tissue is increased by exposure to cold, β-adrenergic agonists and intense physical exercise (26).…”
Section: Discussionmentioning
confidence: 99%
“…They regulate gene expression by functioning as microRNA sponges and by affecting transcription, splicing, and translation (20). Recent research has also demonstrated that lncRNAs are involved in brown adipogenesis, the browning of white adipose tissue, and brown adipose thermogenesis (21). These lncRNAs include lncRNA-BATE1, lncRNA-BATE10, AK079912, Blnc1, H19, Lnc-Uc.417 and Lnc-dPrdm16 (21).…”
Section: Introductionmentioning
confidence: 99%
“…The molecular regulation by RNAs is not limited to small RNAs and increasing evidence has suggested that long non-coding RNAs (lncRNAs) also play a role in beige and brown development and function [ 171 ]. LncRNAs are RNA molecules with more than 200 nucleotides in length and their mechanism of action includes chromatin remodeling, chromatin interactions, natural antisense transcripts (NATs], as well as interacting with RNA binding proteins in the cytosol [ 172 ].…”
Section: Molecular Circuits Regulating Brown and Beige Adipose Tissue Development And Functionmentioning
confidence: 99%